2018
DOI: 10.1177/0363546518799353
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lateral Opening Wedge Distal Femoral Varus Osteotomy on Tibiofemoral Contact Mechanics Through Knee Flexion

Abstract: Background: Lateral opening wedge distal femoral osteotomy (DFO) unloads a diseased lateral compartment of the knee in patients with genu valgum. To the best of our knowledge, there are no biomechanical studies investigating the effect of knee flexion on contact pressure and area after DFO. Hypothesis: As knee flexion angles increase, DFO will be less effective at unloading the lateral compartment of the knee. Study Design: Controlled laboratory study. Methods: Lateral opening wedge DFO was performed, correcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…After a mean follow-up of 40 months, the authors reported clinical improvement and accurate correction [ 51 ]. However, from a biomechanical point of view, it must be noted, that DFO decreases tibiofemoral contact pressure more effectively in extension compared with increasing angles of knee flexion [ 53 ]. Based on knowledge of total knee arthroplasty, HTO should decrease tibiofemoral contact pressure throughout flexion angles [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After a mean follow-up of 40 months, the authors reported clinical improvement and accurate correction [ 51 ]. However, from a biomechanical point of view, it must be noted, that DFO decreases tibiofemoral contact pressure more effectively in extension compared with increasing angles of knee flexion [ 53 ]. Based on knowledge of total knee arthroplasty, HTO should decrease tibiofemoral contact pressure throughout flexion angles [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, from a biomechanical point of view, it must be noted, that DFO decreases tibiofemoral contact pressure more effectively in extension compared with increasing angles of knee flexion [ 53 ]. Based on knowledge of total knee arthroplasty, HTO should decrease tibiofemoral contact pressure throughout flexion angles [ 53 ]. Therefore, it remains unknown whether DFO is as effective as HTO.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Realignment osteotomies are most commonly used in the treatment of osteoarthritis, to shift the weightbearing axis from a diseased articular surface to healthy areas. Osteotomies are also a good option to correct bony deformities and normalize biomechanical properties, such as reduction of locally elevated contact forces, of the knee in patients with congenital or postfracture deformity 1 , 39 or after ligament reconstruction, meniscal transplant, or chondral resurfacing surgery in adversely aligned lower limbs.…”
mentioning
confidence: 99%
“…A femoral-based osteotomy will preferentially affect joint contact forces in extension with less effect at higher knee flexion angles and no effect at 90 or beyond. 10 In these cases, as well as cases with a primary valgus deformity within the tibia, our preference is to perform a tibial based osteotomy. Other complications inherent to osteotomy procedures include nonunion, malunion, wound complications, infection, thromboembolism, stiffness, and painful hardware requiring reoperation.…”
Section: Discussionmentioning
confidence: 99%